(untitled) (Global Journal of Science Frontier Research, 2012)
Introduction - Training is a tool used to empower people so that they are able to lead their own development, solve problems and to participate in meaningful debates of any field of learning. However, training transfer literature asserts that the successful transfer of learning to the workplace is often limited (Baldwin et al., 2009). This trend prevails despite heavy investments of finance, human resources, time and technology in employee training aimed at enhancing worker and organizational performance. There has been very low transfer of learning especially in the Agriculture where the adoption if moisture conservation innovations is very despite heavy investment in all capitals (Andersson and Giller, 2012, Twomlow et al, 2008, Zhou, 2008).This has posed a great challenge in the training of smallholder farmers on new innovations. There is need therefore to find ways of supporting the transfer and application of training for smallholder farmers as they depend mostly on agricultural extensionist trainings for their human resource development.